Nutrient Intakes and Nutritional Status of Mothers and their Under-Five Children in a Rural Community of Oyo State, Nigeria - Fabunmi, T. M.; Onabanjo, O. O.; Oguntona, E. B.; Keshinro, O. O.; Onabanjo, J. A.; Obanla, O. O.; Oyawoye, O. O. (International Journal of Child Health and Nutrition, 2013)
Malnutrition in sub-Saharan Africa contributes to high rates of childhood morbidity and mortality which make it a public health concern in Africa. This study assessed the nutrient intakes and nutritional status of mothers and their under-five children in a rural community of Oyo State, Nigeria. A total of 500 households with a mother and child pair were sampled using a multi-stage sampling procedure. Information on household socio-economic status, hygiene practices, breastfeeding practices and clinical observation for signs of malnutrition were collected using pre-tested semi-structured questionnaires by trained interviewers. Weight for age (WAZ), weight for height (WHZ), and height for age (HAZ) for underweight, wasting and stunting, respectively were calculated and assessed by Epi Info software using the NCHS/WHO international reference values. BMI (weight/height2) of mothers were also constructed from the measurements of mothers’ weights and heights. The waist/hip ratio of mothers was also determined. An interactive 24 h recall repeated for three days was used to obtain data on food and nutrient intakes of the women. Information on foods consumed was converted into quantitative data of nutrients using Food Composition Table. The result showed a high proportion (81%) of mothers ate three times daily while 14% ate twice and 5% ate more than thrice daily. The mean daily intakes of calcium, vitamins A, B6, B12, niacin, and folate were found to be inadequate compared with the Recommended Intakes. The WHR of the mothers indicated that majority had low risk. Most of the mothers (69.2%) were normal, underweight 9.6%, overweight 15.8% and obese 5.4%. About 37% of the children were stunted, 18% were underweight and 14.3% were wasted. BMI correlated negatively with age (r = -0.41; p <0.05), and positively with education (r = 0.22; p<0.05) and income (r = 0.45; p <0.05). Clinical observation revealed PEM prevalence in 12% children while eyes pallor and palm pallor were present in 15% and 20% respectively. The nutritional status of mothers and their under-five children is poor with respect to the overall food consumption and micronutrient intake. Consequently, nutrition programmes in this area should include effective measures to promote nutritional status of mothers and children.